Temporary and substitute income tax regime for declaration, repatriation of capital and investment of undeclared income - Samhan Salgado, Fiorella (2018)
The repatriation of capital is the return of capital of those citizens resident in the country who maintain abroad and is associated with the expectations of the agents regarding the economic future of a country. Repatriation refers to the existence of an action that aims to return those capitals to the country of origin, because companies or individuals who have legally formed a heritage seek not only to protect their capital but also to seek access to the best investment alternatives, which allows them to increase their profits and in some cases further optimize their profitability. It is in this search that is developed in this article that leads to avoid the flight of capital.